Computational Study of Heat Transfer Behavior in Fluid-Solid Fluidized Beds. - Flamarz, Sherko Ahmad (Sulaimani Journal for Engineering Sciences, 2020)
Heat transfer in fluid-solid fluidized beds is investigated using a combined of computational fluid dynamics (CFD) and discrete element method (DEM) approach, incorporated with a thermal model. The approach has taken into account almost all the mechanisms in heat transfer in fluidized beds. A comparison and validation of hydrodynamic and thermal data of fluidized bed obtained using CFD-DEM thermal approach with experimental and numerical results data in the literature is carried out. The simulations results reveal a good thermal steady state during the simulation time for calculating the thermal behaviors of fluidized beds like; the mean particle temperature, bed porosity, heat transfer coefficient and mean particle Reynolds number. The simulations results are showed a good agreement and consistency with the experimental and numerical data in the literatures. Thus, the integration of combined CFD-DEM with the thermal model is a step toward for the prediction, development the heat transfer efficiency in fluid-solid system, and the decrease of energy consumption of the industrial applications.
Keywords: Fluidization; Multiphase flow; Combined CFD-DEM; Heat transfer